Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/pcan.2011.3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting prostate cancer at rebiopsies in patients with high-grade prostatic intraepithelial neoplasia: a study on 546 patients

Abstract: The aim of this study was to analyse the factors that predict the diagnosis of prostate cancer (PCa) after high-grade prostatic intraepithelial neoplasia (HGPIN). Data from 546 patients with HGPIN submitted up to a 6-month series of three rebiopsies, according to an institutional protocol, were reviewed. PCa has been found in 174 cases (31.8%), in 116 cases at the first and in 58 cases at a further rebiopsy. The risk of finding PCa at the first rebiopsy was correlated with the PSA value and with an anomalous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
(25 reference statements)
0
7
3
Order By: Relevance
“… 9 , 10 , 23 Based on these facts, two or more cores of HGPIN on a TRUS-guided biopsy with 10 or 12 cores strongly indicate the presence of PCa. Furthermore, the detection rate (88.9%) of PCa at repeat biopsy in patients who had two or more cores of HGPIN at a previous TRUS-guided biopsy is higher than those of other reports (30.9%, 20 31.8%, 21 and 40% 10 ). The high detection rate of PCa in the present study can be explained as follows.…”
Section: Discussioncontrasting
confidence: 55%
“… 9 , 10 , 23 Based on these facts, two or more cores of HGPIN on a TRUS-guided biopsy with 10 or 12 cores strongly indicate the presence of PCa. Furthermore, the detection rate (88.9%) of PCa at repeat biopsy in patients who had two or more cores of HGPIN at a previous TRUS-guided biopsy is higher than those of other reports (30.9%, 20 31.8%, 21 and 40% 10 ). The high detection rate of PCa in the present study can be explained as follows.…”
Section: Discussioncontrasting
confidence: 55%
“…Many studies have found that clinical parameters, including a patient's age, various forms of serum PSA measurement and abnormal DRE, do not correlate with the cancer risk associated with HGPIN in subsequent biopsy [5,36]. In the present study, we did not find that a patient's age and the number of repeat biopsy sessions were associated with different cancer risk.…”
Section: Discussioncontrasting
confidence: 79%
“…The overall PCa detection rate at repeat biopsy in this series was 38.3%, higher than the 20%–32% in other published reports [3–5]. The difference is probably due to the longer follow‐up in our series.…”
Section: Discussioncontrasting
confidence: 68%
“…The estimated time frame to disease progression after HGPIN findings has been reported to be between 29 and 36 months [5,6]. In addition, an increase in the size and number of HGPIN foci has been associated with both prostate adenocarcinoma and its multifocality [7-13]. HGPIN and carcinoma tend to preferentially involve the peripheral zone of the prostate [8,9], and recently many biomarkers and molecular changes such as TMPRSS2-ERG gene fusion have been described in both entities (as discussed further below) [14,15].…”
Section: Epidemiologymentioning
confidence: 99%
“…This decrease in the incidence of cancer following a diagnosis of HGPIN is likely related to the increase in the number of needle core biopsies taken, which has improved the accuracy of the initial biopsy. As one would expect with a pre-malignant lesion, the rate of cancer detection on repeat biopsy has been strongly correlated with an increasing number of cores (≥2) containing HGPIN in the initial biopsy [7,12,13]. As a result, this has led to the recommendation of repeat prostate biopsy within 1 year of such findings.…”
Section: History and Evolution Of The Definition Of Hgpinmentioning
confidence: 99%